Fluorescein Angiography Scoring System Using Ultra-Wide–Field Fluorescein Angiography Versus Standard Fluorescein Angiography in Patients with Sarcoid Uveitis. (17th November 2021) - Tanaka, Rie; Kaburaki, Toshikatsu; Yoshida, Atsushi; Takamoto, Mitsuko; Miyaji, Tempei; Yamaguchi, Takuhiro
ABSTRACT: Purpose : To compare standard fluorescein angiography (FA) and ultra-wide-field (UWF) FA in evaluating sarcoid uveitis activity using the scoring system adopted by the Angiography Scoring for Uveitis Working Group (ASUWG). Methods : Standard and UWF FA images of 36 eyes with sarcoid uveitis were acquired on the same day. Three graders independently graded 72 FA images using the ASUWG scoring system. We evaluated inter-observer variability using the intra-class correlation coefficient (ICC) and compared scores of each angiographic sign. Results : The ICC was 0.77 for standard FA and 0.87 for UWF FA, with respective total scores of 12.0 and 14.6. UWF FA had higher scores than standard FA for optic disc hyperfluorescence, posterior retinal vascular staining and/or leakage, and peripheral capillary leakage. Conclusions : The scores for UWF FA had a higher ICC than those for standard FA in evaluating sarcoid uveitis. Peripheral capillary leakage scores were particularly high for UWF FA.